PEMANFAATAN BAKTERI PROBIOTIK DARI SALURAN PENCERNAAN AYAM KAMPUNG PADA PEMBUATAN PUPUK ORGANIK CAIR - Saida, Saida; Suriyanti, Suriyanti; Ramli, Muhammad (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
Probiotic bacteria are often used as liquid organic fertilizer supplements. Probiotic bacteria can degrade organic compounds. This research aims to determine the benefits of probiotic bacteria isolated from the digestive tract of free-range chickens in making liquid organic fertilizer and analyzing the nutrients contained in liquid organic fertilizer. Making liquid organic fertilizer by treating types of bacteria from the chicken's digestive tract includes: Bacterial Isolate from Cache 2, Bacterial Isolate from Intestine 3, Bacterial Isolate from Provent 2, Bacterial Isolate from Provent 3, and Bacteria from Provent 4. 500 of each are made. ml and repeated three times. Incubate for three weeks and observe the changes that occur. Observation parameters include changes in color, aroma, and bubbles. Meanwhile, the nutrient analysis of liquid organic fertilizer includes total N, available P, available K, organic C, C/N ratio, and pH. The results of the research show that isolates of probiotic bacteria from the digestive tract of free-range chickens can be used as organic material-degrading microbes in the process of making liquid organic fertilizer. Results of analysis of N, P, K, C-organic, and pH nutrient levels in liquid organic fertilizer treated with probiotic bacterial isolates from the digestive tract of free-range chickens, namely, nitrogen levels in treated bacterial isolates from provent 2 were 0.24%, phosphorus in the treatment of prebiotic bacterial isolates from provent 3, namely 3.80 ppm, Potassium in the treatment of prebiotic bacterial isolates from provent 3, namely 9.99 ppm, C-Organic in the treatment of prebiotic bacterial isolates from the intestine was 4.81% and pH in the treatment of bacterial isolates prebiotics from provent 2 was 3.56.